The Effect of Work Environment and Workload on Employee Turnover Intention Through Work Stress at PT. Metropolitan Land, Tbk Branch Metland Menteng - Ruland Willy Jack Sumampouw; Nur Ajijah; Heddy Setiawan; Ambo Paerah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of the work environment on work stress, the effect of workload on work stress, the effect of work stress on turnover intention, the effect of work environment on turnover intention, the effect of workload on turnover intention, the influence of work environment on turnover intention through work stress, and the effect of workload on turnover intention through work stress at PT. Metropolitan Land, Tbk Metland Menteng branch. This study uses an associative research strategy. Data collection techniques through questionnaires using the Simple random sampling technique. Data analysis was carried out using the SEM-PLS method using SmartPLS 3.0 software. The population of this research is all employees of PT. Metropolitan Land, Tbk Metland Menteng Branch. The sample is determined based on the Slovin formula, with a total of 56 samples. The results of this study indicate that: 1) work environment is significant to work stress; 2) workload is significant to work stress; 3) work stress is significant to turnover intention; 4) work environment is not significant to turnover intention; 5) workload is significant to turnover intention; 6) work environment is insignificant to turnover intention through work stress; and 7) workload is significant to turnover intention through work stress. This study also shows that work stress only mediates workload on turnover intention and does not mediate work environment on turnover intention.